The effectiveness of voriconazole in therapy of Candida glabratas biofilms oral infections and its influence on the matrix composition and gene expression - Rodrigues, Célia F. (2017)
Candida glabrata is one of most prevalente yeast in fungal infections, especially in immunocompromised patients. Its azole resistance results in a low therapeutic response, particularly when associated with biofilms. The main goal of this work was to study the effectiveness of voriconazole (Vcz) against C. glabrata biofilms oral pathologies, as esophageal or oropharyngeal candidiasis. Antifungal susceptibilities were determined in pre-formed 24-h-biofilms and ERG genes expression was determined by qRT-PCR. Protein quantification was performed using BCA Kit, carbohydrate was estimated according to the Dubois assay and b-1,3 glucans concentration were determined using Glucatell kit. Finally, ergosterol, Vcz, and fluconazole (Flu) concentrations within the bio-film matrices were determined by RP-HPLC. Results showed that C. glabrata biofilms were more susceptible to Vcz than to Flu and that ERG genes expression evidenced an overexpression of the three ERG genes in the presence of both azoles. The matrix content presented a remarked decrease in proteins and an increase in carbohydrates, namely b-1,3 glucans. Ergosterol was successfully detected and quantified in the biofilm matrices, with no differences in all the considered conditions. Vcz demonstrated better diffusion through the biofilms and better cell penetration capacities, than Flu, indicating that the structure of the drug molecule fully influences its dissemination through the biofilm matrices. This work showed that Vcz is notably more effective than Flu for the treatment of resistant C. glabrata oral biofilms, which demonstrates a clinical relevance in its future use for the treatment of oropharyngeal/esophageal candidiasis caused by this species.